Effectiveness of Inorganic Fertilizer and Biofertilizer Application on Maize Yield and Fertilizer Use Efficiency on Inceptisol from West Java - Jati Purwani; Nurjaya Nurjaya (UNIVERSITY OF LAMPUNG, 2020)
The study about the effectiveness of inorganic fertilizer and bio-fertilizer application on maize yield and fertilizer use efficiency has been carried out in the greenhouse using Inceptisol from Dukuh Village, Cibungbulang District, Bogor Regency. Inorganic fertilizers used were Urea, SP36 and KCl, the biofertilizer used consisted of Azospirillum sp., Azotobacter sp., Bacillus sp., and Lactobacillus sp.. The study was arranged in a Randomized Block Design consisting of seven treatments and six replications. The treatments consisted of various dosages of inorganic fertilizers combined with bio-fertilizer, namely 1) Control (without fertilizer), 2) 100% recommended NPK level, 3) Biofertilizer, 4) 25% recommended NPK level+Biofertilizer, 5) 50% recommended NPK level+Biofertilizer, 6) 75% recommended NPK level + Biofertilizer, 7) 100% recommended NPK level + Biofertilizer. The results showed that the application of inorganic NPK ferttilizers and biofertilizer on maize cultivation on Inceptisol from Dukuh Village, Cibungbulang District, Bogor Regency resulted in an increase of maize yield compared to the recommended level of inorganic fertilizers (100% NPK). The treatment of NPK (50% recommended level)+Biofertilizer resulted in the highest biomass dry weight, yield of corn and value of RAE (Relative Agronomic Effectiveness). The shoot dry weight was 138.09 g pot-1, corn yield was 190.87 g pot-1, and RAE value was 113.44%. The optimum doses of NPK fertilizers were 200 kg Urea ha-1, 60 kg SP-36 ha-1 and 45 kg KCl ha-1 combined with 4 L ha-1 biofertilizer.